Up-to-date statistical essentials in climate change and hydrology: A review - Şen, Zekai (Inderscience Publishers Ltd, 2020)
In climatology and hydrology probabilistic, statistical and stochastic analyses are frequently used tools for the identification of changes and variability within uncertainty domain. There are different statistical-based methodologies for climate change and hydrology data modelling, future simulation and projection studies. Although integro-differential conservation equations provide the dynamic basis, but due to uncertainty ingredients probabilistic and especially statistical calculation principles are panaceas for better solutions. In the literature, there are many articles, where the proper usages of the statistical methodologies are rather weak, incomplete or even to a certain extent not acceptable. The main reason might be in many cases use of ready software without knowing the rational, logical and practical background principles of the statistical methodologies with their validity of restrictive assumptions. There are numerous statistical methods with their special pros and cons. This review paper covers the main applications of statistical methods in climate change and hydrology studies.
Keywords: Assumptions; Climatology; Hydrology; Methodologies; Parameters; Pitfalls; Statistics; Trends; Uncertainty